Comparative Analysis on the Solutions of Hydrogen Production Using Solar Energy with and without Connection to the Power Network. (2016) - Naghiu, George Sebastian; Giurca, Ioan; Aschilean, Ioan; Badea, Gheorghe
Abstract: This paper develops for the first time in the field of the solar technologies, the concept of a system that can simultaneously produce more than three types of energy. This is possible due to the modular conception, namely the conception of standardized modules as a solution for attracting and concentrating the solar radiation, but also different depending on the component which converts the energy. The study meets the European Union's policy whose target is the transition to an economy based on hydrogen produced from renewable sources by the middle of the 21 st century. According to this study, starting with 2030 it is possible that the price of hydrogen may be competitive as compared to the price of heavy oil.